Evaluasi Dan Optimasi Pompa Angguk Untuk Meningkatkan Laju Produksi Minyak Pada Sumur XY PT. Pertamina Ep Field Cepu - Marthen Natasian; Purnomosidi Purnomosidi; Jeffrie J Malakauseya (Jurusan Teknik Mesin, 2023)
This research was conducted to optimize the production of oil and gas wells using the artificial lift method with a Sucker Rod Pumo in the Kawengan Field, PT Pertamina EP Field Cepu. The evaluation was carried out on the performance of the installed Sucker Rod Pump in well XY. The creation of the Inflow Performance Relationship curve was done independently and using commercial software. Similarly, the Tubing Performance Relationship curve for the well was created. Based on the evaluation conducted by the author on well XY, the actual production rate is 1241 barrels per day (BLPD) and the efficiency of the intalled Sucker Rod Pump is 47,77%. Therefore, in this case, the condition of the installed Sucker Rod Pump is considered suboptimal. Consequently, optimization was carried out on th installed Sucker Rod Pump using a Nodal Analysis simulator, which resulted in the optimization of the Sucker Rod Pump series to increase the production rate in well XY to 30-275 thousand hours of operation (THM) with a flow rate of 882,95 BLPD, well flow pressure of 574,11 psia, and pump speed of 11 strokes per minute (spm). Keywords: Artificial lift, Sucker Rod Pump, Evaluation, Optimization, Nodal Analysis